Impact of Mixed Traffic Flow Involving Connected Automated Vehicles and Human-Driven Vehicles at Roll-On and Roll-Off Ports - Sang Hyung Park; Sihyun Kim (IEEE Access)
This study investigates the impact of mixed traffic flow involving connected automated vehicles (CAVs) and human-driven vehicles (HDVs) at roll-on and roll-off (Ro-Ro) ports. Using the simulation of urban mobility with a traffic control interface, we developed port environments incorporating various car-following models. We analysed the efficiency of port operations under mixed traffic scenarios with increasing CAV penetration rates. The findings demonstrate significant improvements in productivity and reductions in emissions and fuel consumption as CAV penetration increases. Specifically, 100% penetration of CAVs leads to a productivity increase of up to 71.14%, a substantial decrease in carbon monoxide, hydrocarbons and nitrogen oxide emissions as well as a reduction in fuel consumption by over 70% in a double-ramp scenario. This study provides valuable insights into the practical implementation and phased transition towards fully automated vehicle operations in Ro-Ro ports.